Strategi Pembelajaran Berdiferensiasi pada Pembelajaran Matematika Materi Keliling Bangun Datar Kelas IV Sekolah Dasar - Linda Wardhatul Hasanah; Hernawi Silalahi; Novianto Bhakti Putra Utama (Jurnal Didaktika Pendidikan Dasar, 2023)
The learning process carried out by teachers in schools still has many problems because it is faced with the diversity of student characteristics. This study aims to determine the increase in activity and student learning outcomes through the application of differentiated learning in mathematics learning the material around flat shapes for class IV SD Negeri 129 Rejang Lebong through Classroom Action Research (PTK). This research is a class action research with procedures consisting of four main components of class research namely planning, action, observation, and reflection in 2 cycles. The instruments used in this study were student activity observation sheets and tests. Research data were analyzed using quantitative data analysis techniques and qualitative data. There was an increase in student activity and learning outcomes, from an average score of 56.42 in pre-cycle to 64.28 at the end of cycle II. It can be concluded that the application of differentiated learning in mathematics learning material around flat shapes for class IV SD Negeri 129 Rejang Lebong can increase student activity and learning outcomes.